Changing performance of surgical risk scores according to the endpoint of postoperative mortality in infective endocarditis patients - Gatti, Giuseppe; Fiore, Antonio; Ismail, Maria; Vendramin, Igor; Minati, Alessandro; Sinagra, Gianfranco; Perrotti, Andrea; Mazzaro, Enzo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe optimal endpoint for reporting early mortality after cardiac operations for infective endocarditis (IE), as well as the optimal mortality target for surgical risk scores, are unresolved questions.MethodsFive risk scores created specifically to predict early mortality after cardiac operations for definite IE, and the European System for Cardiac Operative Risk Evaluation II, were assessed in terms of calibration, discrimination and accuracy in predicting early mortality following cardiac surgery for IE. The evaluation was based on five definite endpoints of postoperative mortality: In-hospital, 30-day, in-hospital/30-day, six-month, and one-year mortality. The six risk scores were tested in a population of 991 patients with definite IE who underwent 1,014 cardiac operations at five European university-affiliated centers.ResultsThere were 133 (13.1%) hospital deaths after surgery. Overall, 10% of patients died within 30 days after surgery, 10.4% of survivors died between 30 days and six months after surgery, and another 5.5% between six months and one year after surgery. All risk scores showed good prediction accuracy and at least acceptable discrimination for all endpoints of postoperative mortality. However, only one (IE-specific) risk score exhibited acceptable calibration for every endpoint of postoperative mortality.ConclusionsSince mortality decreases slowly throughout the first year after cardiac surgery for IE, it may be appropriate to report both in-hospital and one-year mortality (coupled endpoint) for this condition. For both endpoints, only one of the risk scores considered in this study showed acceptable calibration and discrimination.